Model Interpretasi al-Qur'ān Abdullah Saeed - Achmad Zaini (Islamica: Jurnal Studi Keislaman, 2011)
This article tries to deliver Abdullah Saeed's idea on the new approach to interpret the Qur'ān called contextualist approach. He proposes his ideas based on his finding that there is a gap between texts which have been understood literally by majority of ulama? and socio-historical context of the Qur'ān at the time of revelation in the first/seventh century and the contemporary concerns and needs of Muslims today. Based on his expertise on hermeneutic, he proposes four stages: encounter with the world of the text, critical analysis, meaning for the first recipients and meaning for the present. The proposed idea should be appreciated even though it seems that it is a preliminary study which has to be elaborated into practical way.